Diagnostico poblacional de lissorhoptrus sp. en el cultivo de arroz - valle del Bajo Mayo - Ramírez Pinedo, Juan Carlos (2006)
This research paper entitled Diagnosis • Population Lissorhoptrus sp. in rice cultivation - VaJle the Bajo Mayo objectives were to estimate the population of adults, larvae and pupae of Lissorhoptrus sp. in rice cultivation, Valle del Bajo Mayo and identify the species of Lissorhoptrus sp. in rice cultivation, Valle del Bajo Mayo. This work was reafiz6 in the various committees of Irrigators Valley Bajo Mayo corresponding to the provinces of San Martin and Lamas; during the months of April to June 2005. Also the results were subjected to a complete design Az.ar (OCA) with 21 treatments (irrigators Committee) and the comments varied according to the number of farmers in each committee. The results showed that irrigation committees Porvenir, San Rafael, San Juan de Cumbaza, San Juan Bautista, Cocopa Union and Shupishiña obtained averages 733.4; 541.6; 443.4; 318.8; 316.2 and 306.2 juveniles per m2, were those that registered the largest populations of Lissorhoptrus gracllipes. The increased presence of Lissorhoptrus gracilipes was obtained when the crop had 30 to 50 days after transplantation. In the valley of Bajo Mayo pablación an average of 194.7 larvae it was recorded; Adults and pupae 35,5 43,4 m2. The species identified in the rice fields of the various committees of irrigators Valley Bajo Mayo was Lissorhoptrus gracilipes Kuschel, according to SENASA - MINAG. (See Annex No. 05)